Penyelenggaraan Pendidikan Pada Masa Pandemi di Sekolah Dasar Inklusif - Endang Rochyadi; Tryastuti Irawati Belliny Manullang; Sunardi Sunardi (Jurnal Pendidikan Kebutuhan Khusus, 2021)
The Coronavirus Disease (COVID-19) pandemic occurred in Indonesia since early March 2020 which was then followed by a learning from home policy. The purpose of this study was to gather information through a survey about the implementation of online learning carried out by teachers who provide inclusive education at the Elementary level. The data was collected by using a survey technique and then a descriptive analysis was carried out with a total of 80 respondents from several provinces in Indonesia such as West Sumatra, West Java, Yogyakarta, and East Kalimantan. The results showed during the COVID-19 pandemic has made teachers make changes in the teaching and learning process, but not all teachers use television programs as a medium of learning. The ability of teachers to use ICT helps them in providing educational services and the majority have no difficulty using learning applications. Although at the beginning of the pandemic, it was difficult to adapt learning, but until this article was written the teachers had adapted their learning.